2017
DOI: 10.1021/acscatal.7b00735
|View full text |Cite
|
Sign up to set email alerts
|

Effective and Highly Selective CO Generation from CO2 Using a Polycrystalline α-Mo2C Catalyst

Abstract: Present experiments show that synthesized polycrystalline hexagonal α-Mo 2 C is a highly efficient and selective catalyst for CO 2 uptake and conversion to CO through the reverse water gas shift reaction. The CO 2 conversion is ~16% at 673 K, with selectivity towards CO > 99%. CO 2 and CO adsorption is monitored by DRIFTS, TPD, and show that polycrystalline α-Mo 2 C is an economically viable, highly efficient, and selective catalyst for CO generation using CO 2 as a feedstock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
169
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(178 citation statements)
references
References 58 publications
7
169
2
Order By: Relevance
“…4). It is also important to note that such elongated C-O bond lengths would imply lower barriers for further reduction, 44,80 which in turn would suggest that surfaces from the elongated single bond series could be expected to have lower CO 2 dissociation barriers, even if their adsorption is less exothermic than that seen in a comparable surface from the double bond elongation series.…”
Section: Carbon Dioxide Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…4). It is also important to note that such elongated C-O bond lengths would imply lower barriers for further reduction, 44,80 which in turn would suggest that surfaces from the elongated single bond series could be expected to have lower CO 2 dissociation barriers, even if their adsorption is less exothermic than that seen in a comparable surface from the double bond elongation series.…”
Section: Carbon Dioxide Activationmentioning
confidence: 99%
“…[39][40][41][42] Recently, combined experimental and computational studies have confirmed that TMCs catalyse CO 2 reduction to CO, as the first step in hydrogenation. 43,44 Our previous work has used periodic Density Functional Theory (DFT) calculations to study a large range of bulk and surface properties of TMCs, which indicated that the low-index surfaces of TiC, VC, ZrC and NbC could be highly active in catalysing CO 2 reduction. 45 This work focuses on carbides with 1 : 1 stoichiometries and rock-salt structures, which are only consistently found with carbides that include metal from group 3-5 metals.…”
Section: Introductionmentioning
confidence: 99%
“…The FeNi 3 NPs exhibited a moderate conversion of 8.6 %. Importantly, the optimized FeNi 3 @NG achieved the exceptional conversion of 20.2 %, which is higher than that of the previously reported state‐of‐the‐art materials on the identical conditions (Table S5) . Moreover, FeNi 3 @NG showed a high CO selectivity (near 100 %) without the formation of CH 4 and an exceptional CO evolution rate of 100 mL min −1 g cat −1 , which is two orders of magnitude higher than that of the Ir sample at 1273 K (Table S5) .…”
Section: Figurementioning
confidence: 99%
“…The process that occurs during the CO 2 reduction over FeNi 3 @NG catalyst consists of four‐steps: i) Initial adsorption/activation of CO 2 and H 2 molecules; ii) the formation of CO* and O* intermediates (* represents the surface‐adsorbed species) from CO 2 dissociation; iii) the formation of CO and H 2 O; iv) desorption of the final products from catalyst surface (Figure a) . The adsorption and chemical activation of the inert CO 2 molecule is commonly considered as the kinetically relevant step and the cleavage of C=O bond as the rate‐determining step (RDS); which can be considerably stimulated by the metal‐based catalyst with prominent electronic modulation. A good catalyst for CO 2 reduction should have an appropriate free energy for CO 2 adsorption to surpass the reaction barriers .…”
Section: Figurementioning
confidence: 99%
“…[4a,c, 6a, 7] Recent successful investigation of cobalt-modified molybdenumc arbide( Co-Mo 2 C) wasr eportedt od ecompose CO 2 gas with ac onversion of 9.5 %a nd CO selectivity of 98.1 %a t5 73 K. [4b] Furthermore, K-promoted Mo 2 C( K-Mo 2 C/g-Al 2 O 3 )a sa na ctive and selective catalystachieved high efficiency for CO 2 conversion of 40 %a tr elatively high temperature of 723 K. [8] Polycrystalline hexagonal a-Mo 2 Cw ith ac onversion of 16 %a nd CO selectivity of > 99 %a t6 73 Kw as also realized. [9] However,t he development of ac ost-effective catalytic system to enable the cleana nd efficient decomposition of CO 2 to CO at low temperatures is still required.…”
Section: Introductionmentioning
confidence: 99%